The Analysis of The Problem-Solving Ability of The Ethnomatematcs Nuanced Plane Figure In The Sipirok Woven Fabrics Pattern To MTs Students - Harahap, Amelina; Hasanah, Rusi Ulfa (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
The ability to solve problems is one of the goals of mathematics education. The aim of this study was to describe the problem-solving skill of students in class VII-1 of MTsL 3 Tapanuli Selatan on the material of the Plane figure with ethnomathematical nuances of Sipirok woven fabrics patterns. This qualitative descriptive research involved 25 students of class VII-1 MTsN 3 Tapanuli Selatan as the subjects. Data collection techniques included problem-solving skills tests and interview papers. The results showed that the student's problem-solving skills based on the steps Polya, flat geometric material with ethnomathematical nuances for class VII-I, belonged to the low category with an average percentage of 55.4% and the step indicator more dominant of the polya was an indicator understanding the problem with 80% capture.